Population pharmacokinetic analysis and dosing regimen optimization of teicoplanin in critically ill patients with sepsis - Chen, Chao‐Yang; Xie, Min; Gong, Jun; Yu, Ning; Wei, Ran; Lei, Li‐Li; Zhao, Si‐Miao; Li, Ruo‐Ming; Dong, Xiu; Zhang, Xiang‐Lin; Zhou, Ying; Li, Shuang‐Ling; et al. (Frontiers in Pharmacology, 2023)
Objectives This study aimed to investigate the population pharmacokinetics (PPK) characteristics of teicoplanin in adult sepsis patients and provide recommendations for optimal teicoplanin dosing regimens. Methods A total of 249 serum concentration samples from 59 septic patients were prospectively collected in the ICU. Teicoplanin concentrations were detected, and patients’ clinical data were recorded. PPK analysis was performed using a non‐linear, mixed‐effect modeling approach. Monte Carlo simulations were performed to evaluate currently recommended dosing and other dosage regimens. The optimal dosing regimens were defined and compared by different pharmacokinetic/pharmacodynamic parameters, including trough concentration (Cmin), the ratio of 24-h area under the concentration-time curve to the minimum inhibitory concentration (AUC0-24/MIC), as well as the probability of target attainment (PTA) and the cumulative fraction of response (CFR) against MRSA. Results A two-compartment model adequately described the data. The final model parameter estimates for clearance, central compartment volume of distribution, intercompartmental clearance and peripheral compartment volume were 1.03 L/h, 20.1 L, 3.12 L/h and 101 L, respectively. Glomerular filtration rate (GFR) was the only covariate that significantly affected teicoplanin clearance. Model-based simulations revealed that 3 or 5 loading doses of 12/15 mg/kg every 12 h followed by a maintenance dose of 12/15 mg/kg every 24 h to 72 h for patients with different renal functions were required to achieve a target Cmin of 15 mg/L and a target AUC0-24/MIC of 610. For MRSA infections, PTAs and CFRs were not satisfactory for simulated regimens. Prolonging the dosing interval may be easier to achieve the target AUC0-24/MIC than reducing the unit dose for renal insufficient patients. Conclusions A PPK model for teicoplanin in adult septic patients was successfully developed. Model-based simulations revealed that current standard doses may result in undertherapeutic Cmin and AUC, and a single dose of at least 12 mg/kg may be needed. AUC0-24/MIC should be preferred as the PK/PD indicator of teicoplanin, if AUC estimation is unavailable, in addition to routine detection of teicoplanin Cmin on Day 4, follow-up therapeutic drug monitoring at steady-state is recommended.